THE STATE, STRUCTURE AND DYNAMICS OF DOMESTIC VIOLENCE IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2023)
The proposed article is devoted to the criminological characteristics of domestic violence and its problematic issues. In the course of the study, the authors focused on the problems of prevention and the causes of domestic violence. The article analyzes important statistical and criminological indicators of domestic crime and its spread by types of criminal offenses, which allow us to present in a generalized form a system of statistical data revealing, including qualitative originality, trends and patterns of crime of the type under consideration. In particular, the article provides current percentages of victims (in many cases, women and children) of domestic violence by type of this socially dangerous act, and also analyzes the portrait of the criminal.The importance of indicators of the state, structure, dynamics of family and household crime in the implementation of crime prevention measures is described. In the conclusion of the article, the authors identified the causes of the spread of crime in the family sphere, based on the data of the Committee on Legal Statistics under the Prosecutor General's Office of the Republic of Kazakhstan, also provided methodological recommendations for improving state policy in the field of prevention of domestic violence and improving crime prevention measures in this area.Keywords: crime, domestic crime, crime indicators, crime status, dynamics, proportion, trends, forecasting, criminogenic activity, preventive measures, informative characteristics.